Professionalization of heritage conservation architects in the Philippines - Dullas, Arianne Joy Q. (College of Architecture, University of the Philippines Diliman, 2018)
The research conducts a study about the establishment of a professionalization system for heritage conservation architects in the Philippines. It first tackles the rationale to justify the need for creating it. This is done through studies on the problems that are being encountered by heritage structures and clients, as well as the opportunities that could be opened to the industry using the development of the system. Through studies on existing professionalization abroad, particularly with the United Kingdom and Japan, the current situation of the local practice is compared to analyze its condition today, if it is still in an acceptable level or a development is badly needed. Specifically, the architect's liability towards these problems is analyzed. This is done to determine if the quality of work that the local professionals, such as an architect, is satisfactory. Criteria that are being used by UK and Japan in their professionalization is considered to analyze if the said practitioners are qualified for the job. A proposal for developing an accreditation system is projected to address the need according to the current situation of the practice. With this, a sound criteria for the practitioners is needed to serve as a foundation for future plans of recognizing heritage conservation architects in the Philippines. It attempts to categorize the practitioners' knowledge in the field through looking into the levels. This does not only determine the scope and limitation of works of accredited heritage architects based on their expertise, but it also defines the benefits that they will be acquiring. Keywords: Heritage conservation, professionalization, accreditation